Calf immunology and the role of vaccinations in dairy calves. Issue 3 (6th April 2018) - Sherwin, Ginny; Down, Peter
Abstract : The risk of mortality and morbidity in calves is highest during the first few weeks of life. The main causes of mortality change throughout the preweaning period: septicaemia is most likely to occur in neonatal calves (up to 28 days of age); diarrhoea in calves less than 30 days old, and bovine respiratory disease in dairy calves more than 30 days old (McGuirk 2008). During this critical period, many producers look to vaccination and other preventive interventions to minimise the risk of disease. This article discusses the role of vaccinations in the rearing of dairy calves, alongside other preventive measures, and considers the immunological changes that occur during the first few weeks of a calf's life that are intrinsically linked with risk of morbidity and subsequent mortality in calves.